1989
DOI: 10.1007/bf03350711
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional state on the disposal of orally and intramuscularly administered iodized oil to iodine repleted older children and adult women

Abstract: Iodinated oil (Ethiodol, 1 or 2 ml) was administered po or by im administration to adult women and older children in rural highland Ecuador who were either well nourished or malnourished to determine the effect of nutritional status on the disposal rate of iodine. These subjects resides in a region previously severely deficient in iodine, but this had been corrected in these subjects by prior administration of iodinated oil or by use of iodized salt or both. Malnutrition as determined by the conventional stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Maternal iodine deficiency in early pregnancy and associated thyroxine deficiency impair the development of the fetal central nervous system and can result in frank, irreversible cretinism in the child. Studies in Ecuador (Fierro-Benitez et al, 1989;Trowbridge, 1972) showed that correction of the maternal iodine deficiency before conception or in early pregnancy can improve the mental performance of offspring. Comparisons of primary school children in China, in areas with iodine deficiency versus areas with normal iodine intake (Ma, Wang, Wang, Chen, & Chi, 1989) and of goitrous vs. non-goitrous children in Chile (Muzzo, Levia, & Carrasco, 1987) showed better mental and psychomotor performance in the latter groups.…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%
“…Maternal iodine deficiency in early pregnancy and associated thyroxine deficiency impair the development of the fetal central nervous system and can result in frank, irreversible cretinism in the child. Studies in Ecuador (Fierro-Benitez et al, 1989;Trowbridge, 1972) showed that correction of the maternal iodine deficiency before conception or in early pregnancy can improve the mental performance of offspring. Comparisons of primary school children in China, in areas with iodine deficiency versus areas with normal iodine intake (Ma, Wang, Wang, Chen, & Chi, 1989) and of goitrous vs. non-goitrous children in Chile (Muzzo, Levia, & Carrasco, 1987) showed better mental and psychomotor performance in the latter groups.…”
Section: Micronutrient Deficienciesmentioning
confidence: 99%